(untitled) (Research, Society and Development, 2023)
Buriti is used as food in several culinary recipes by the amazonian population. The rind and pulp of the fruit contain minerals, dietary fiber, essential oils and total carotenoids. Therefore, this work aimed to enrich the nutritional composition of French bread, which has carbohydrates as its predominant nutrient, through the addition of the aqueous extract of the fruit pulp. After pre-tests, the concentrations of 50, 100 and 150 mL of extract to be added to the mix with wheat flour to prepare the dough were determined. In the buriti pulp extract, as well as in the breads formulated with different concentrations of extract, analysis of centesimal composition, functional compounds and microbiological pattern were carried out. The standard and experimental breads presented similar proximate composition for ash, protein and dietary fiber contents. However, breads containing buriti extract had lower levels of lipids, carbohydrates and calories compared to standard French bread. Microbiological analyzes showed suitable food safety, because the absence of the microorganisms analyzed, accrediting them to be used as a nutritional and healthy food, thus providing benefits to the health of the consumer.